Enhancing Competence, Environmental Management System, Job Satisfaction and Employee Performance - MULYANTO, MULYANTO; AWATARA, I Gusti Putu Diva; GUNARDI, Ardi (Journal of Environmental Management and Tourism, 2018)
This study is aimed at finding out the effect of competence and environmental management system on the employee performance at Regional Company Taman Satwa Taru Jurug Surakarta and the effect of job satisfaction in mediating the effect of competence and management system on the employee performance at Regional Company Taman Satwa Taru Jurug Surakarta. This research is a survey research conducted at Regional Company Taman Satwa Taru Jurug Surakarta. The population is the study is all employees of Regional Company Taman Satwa Taru Jurug Surakarta totaling 104 employees. The sample in this study is the same as population. The sampling technique used is census where all members of the population are used as a sample. The results showed that the competence and the environmental management system have a significant effect on employee performance at Regional Company Taman Satwa Taru Jurug Surakarta and the job satisfaction can improve the effect of competence and performance management system on employee performance at Regional Company Taman Satwa Taru Jurug Surakarta.